Painful swelling after a noxious event and the development of complex regional pain syndrome 1: A one‐year prospective study. (2nd June 2017) - Brunner, F.; Bachmann, L.M.; Perez, R.S.G.M.; Marinus, J.; Wertli, M.M.
Abstract: Background: The timing of diagnosis of complex regional pain syndrome (CRPS) 1 remains a challenge due to the large heterogeneity of clinical presentations. We describe the distribution and differences in outcomes and clinical manifestations between time points and patient groups with and without CRPS 1 following an initiating event. Methods: Prospective cohort study with a consecutive registration of patients presenting with painful swelling of the affected extremity after an initiating event and follow‐up visits after 3, 6 and 12 months. Results: Forty‐two patients were enrolled (37 females, mean age 55.1 years). At baseline, 35 participants (83%, females n = 30) fulfilled the diagnostic criteria for CRPS 1. At 3 months, 19 out of the initial 35 CRPS 1 patients (54%) did not meet the diagnostic criteria anymore. Besides our inclusion criteria of a painful swelling, early manifestations indicating a CRPS 1 primarily include an impaired quality of life (SF‐35, EQ5‐D), more pain (NRS, MPQ) and restricted range of motion. Conclusions: CRPS 1 develops within 8 weeks following a noxious event. Although many CRPS 1 patients reach partial remission within the first 3 months, signs and symptoms do not improve significantly at 1 year. In order to identify prognostic risk factors large prospective cohort studies are needed. Significance: This prospective cohort study follows patients with complaints most suspected for complex regional pain syndrome (CRPS) 1. CRPS 1 develops within 8 weeks following a noxious event. Although many CRPS 1 patients reach partial remission within the 3 months, symptoms do not improve significantly at 1 year.